Quantitative anti-HBc combined with quantitative HBsAg can predict HBsAg clearance in sequential combination therapy with PEG-IFN-α in NA-suppressed chronic hepatitis B patients - Wang, Wen-Xin; Jia, Rui; Gao, Ying-Ying; Liu, Jia-Ye; Luan, Jun-Qing; Qiao, Fei; Liu, Li-Min; Zhang, Xiao-Ning; Wang, Fu-Sheng; Fu, Junliang (Frontiers in Immunology, 2022)
Background & aims: Precise predictors are lacking for hepatitis B surface antigen (HBsAg) clearance under the combination therapy of nucleos(t)ide analogs (NAs) and pegylated interferon-alpha (PEG-IFN-α) in patients with chronic hepatitis B (CHB). This study aimed to determine the quantitative anti-hepatitis B core antibody (qAnti-HBc) and quantitative hepatitis B core-related antigen (qHBcrAg) as predictors for HBsAg clearance in NAs-suppressed patients with CHB receiving PEG-IFN-α add-on therapy. Methods: Seventy-four CHB patients who achieved HBV DNA suppression (HBV DNA < 20 IU/ml) and quantitative HBsAg (qHBsAg) < 1500 IU/ml after ≥ 1 year of NAs treatment were enrolled. Fifteen patients continued on NAs monotherapy, while 59 patients received PEG-IFN-α add-on therapy. Serum qAnti-HBc and qHBcrAg levels were detected every 12 or 24 weeks for add-on and NAs alone groups, respectively. Results: Serum qAnti-HBc but not qHBcrAg levels at baseline were negatively correlated with duration of prior NAs therapy. After 48-week treatment, both qAnti-HBc and qHBcrAg levels declined further, and 17/59 (28.81%) and 0/15 (0%) achieved HBsAg clearance in add-on and NAs groups, respectively. In add-on group, the rate of HBsAg clearance was significantly higher in patients with baseline qAnti-HBc < 0.1 IU/ml (52.63%). Logistic regression analysis identified baseline qAnti-HBc but not qHBcrAg was an independent predictor for HBsAg loss. Receiver operating characteristic curve analysis showed that the combination of qAnti-HBc and qHBsAg had a better predictive value for HBsAg clearance. Conclusions: A combination of qHBsAg and baseline qAnti-HBc levels may be a better prediction strategy for HBsAg clearance in NAs-suppressed CHB patients receiving PEG-IFN-α add-on therapy.